Prognosis influence of additional chromosome abnormalities in newly diagnosed acute promyelocytic leukemia with t(15;17)(q24;q21) - Lin Liu; Jinghan Wang; Huan Xu; Shuqi Zhao; Lu Wang; Jiansong Huang; Huanping Wang; Hongyan Tong; Jie Jin (Hematology)
Objectives In patients with acute promyelocytic leukemia (APL), additional chromosomal abnormalities (ACAs) are prognostic indicators. However, the clinical features of ACAs were not systematically reported in Chinese patients. Therefore, we enrolled a large cohort of APLs to demonstrate the clinical characteristics and prognostic value of ACAs.Methods 268 patients with newly diagnosed APL with t(15;17)(q24;q21) were retrospectively enrolled, and their clinical characteristics and the predictive value of ACAs were assessed between patients with the presence and absence of ACAs.Results APL patients with and without ACAs did not differ significantly in their clinical features or treatment response and clinical outcomes like overall survival (OS) and disease-free survival (DFS). It appeared to be substantially associated with worse OS in APL patients with trisomy 8, which was the most common ACA, although DFS was unaffected. Interestingly, the presence of ACAs or trisomy 8 affected OS and DFS in the subgroup of patients aged ≥60 years; by contrast, ACAs had no effect on OS or DFS in any treatment subgroup (ATRA + ATO/RIF or ATRA + ATO/RIF + CH or ATRA + CH), except for the ATRA + ATO/RIF + CH treatment subgroup, where their impact on DFS was less favorable.Conclusions Our results suggested that OS and DFS were unaffected by ACAs. Nonetheless, in the subgroup of patients older than 60, the existence of ACAs or trisomy 8 appeared to impact OS and DFS negatively. Individuals with t(15;17) alone had a higher DFS and were more susceptible to ATRA + ATO/RIF + CH than individuals with t(15;17) ACAs.